Difficulties and errors in the diagnosis of primary syphilis in proctological practice (analysis of clinical cases) - N. K. Levchik; V. I. Surganova; N. V. Zilberberg; M. V. Ponomareva (Лечащий Врач)
We report three cases of primary syphilis firstly diagnosed as rectal neoplasma and paraproctitis and describe the clinical and laboratory features of the diseases. Diagnostic problems of primary syphilis are discussed. Specialists should be aware of the possibility of syphilis when confronted with anorectal pathology in order to avoid incorrect diagnosis, inappropriate treatment, and delayed antibiotic therapy, and should gather a detailed history about sexual preferences, including homosexuality.